1998
DOI: 10.1097/00003246-199805000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Acute-phase response of the rat pancreas protects against further aggression with severe necrotizing pancreatitis

Abstract: The acute-phase response of the pancreas seems to be a powerful emergency defense mechanism against further pancreatic aggression, as shown by the improved survival of the animals. The factors mediating this protection are unknown. Due to the strong overexpression of the pancreatitis-associated protein I during the climax of the acute phase, this protein might be involved in the defense mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…), it was speculated that PAP could act as a cell response to the inflammatory stress. This is in line with the fact that induction in the pancreas of an acute-phase response, in which PAP expression was activated, prior to triggering necrotizing pancreatitis, significantly improved the survival of the animals [36] . Studies demonstrated that the administration of anti-PAP antibodies in an experimental model of taurocholate-induced acute pancreatitis in rats was associated with increased inflammation in the pancreas, evidenced by more abundant necrosis, increased pancreatic myeloperoxidase (MPO) levels and more prominent neutrophil infiltration [37] .…”
Section: Pap As An Anti-inflammatory Mediatorsupporting
confidence: 78%
“…), it was speculated that PAP could act as a cell response to the inflammatory stress. This is in line with the fact that induction in the pancreas of an acute-phase response, in which PAP expression was activated, prior to triggering necrotizing pancreatitis, significantly improved the survival of the animals [36] . Studies demonstrated that the administration of anti-PAP antibodies in an experimental model of taurocholate-induced acute pancreatitis in rats was associated with increased inflammation in the pancreas, evidenced by more abundant necrosis, increased pancreatic myeloperoxidase (MPO) levels and more prominent neutrophil infiltration [37] .…”
Section: Pap As An Anti-inflammatory Mediatorsupporting
confidence: 78%
“…Expression of the antiproliferation gene encoding TIS21 is induced upon DNA damage in cell lines, while cells with a targeted disruption in the TIS21 gene fail to undergo cell cycle arrest in response to DNA damage (48). In addition, TIS21 expression is induced in kidney and liver during acute pancreatitis and is thought to play a role in the control of apoptosis progression in these tissues (11).…”
Section: Resultsmentioning
confidence: 99%
“…REG3A is indeed an acute phase protein with an exocrine nature, whose synthesis and processing follows the acinar cell secretory pathway, from the endoplasmic reticulum to the zymogen granules [29,30]. REG3A was shown to act as a protective factor against pancreas damage [19,31,32]. It is therefore remarkable that the rise in the concentration of secretory pathwayassociated proteins observed by proteomic analysis and immunoassays coincided with the burst of REG3A expression.…”
Section: Discussionmentioning
confidence: 95%